Comparison of self-referencing techniques for photothermal detection of trace compounds in water - Hodgkinson, Jane; Johnson, Mark; Dakin, John P. (Elsevier, 2000)
Self-referencing techniques are compared for a closed-cell photothermal detector that uses a water meniscus as a pressure sensor. Deflection of the meniscus was measured using an optical fibre Fabry–Perot interferometer. For long measurement integration times, interference fringe drift was a serious limitation on the detection repeatability for non self-referenced measurements. Two self-referencing techniques were compared for measurements of optical absorption. The first technique used a simultaneous reference absorption signal at a second wavelength, and the second used a simultaneous volumetric modulation within the cell. Both methods have been evaluated with photothermal excitation by a 658-nm LED, a 478-nm LED and a UV discharge lamp. For the detection of absorption in aqueous solutions, the two methods had similar performance. However, the volumetric method could be used for detection of any absorbing compound, regardless of its absorption spectrum and was more convenient to use.
Keywords: Photothermal; Photoacoustic; Spectroscopy; Fibre optic interferometry; Water